To raise or not to raise: Impact assessment of Russia's gas price reform - Christophe Heyndrickx; Victoria Alexeeva-Taleebi; Natalia Tourdyeva (European Regional Science Association (ERSA), 2014)
One of grand challenges which are faced by Russia today is to deregulate its gas market while favouring longer-term growth of economy. Since the 1990s, several proposals for structural reforms of Russian gas industry have been intensively debated, including the split-up of Gazprom. From the mid-2000s onwards, the key component of the reforms has become the introduction of a new pricing scheme for natural gas supply at the domestic markets. This is claimed to fit in a policy promoting energy efficiency, increasing investments in natural gas production and bringing the natural gas price on the domestic market closer to long term cost recovery. Underpricing of natural gas at the domestic markets was an explicit feature of the Soviet era, aimed at stimulating industrial growth. In the post-Soviet period, domestic gas prices were kept at relatively low levels to back up economic recovery, though this strategy had become increasingly untenable by 2006 in the light of Gazprom's investment needs into new extraction fields. A number of studies supported an upward price correction as a prerequisite for any structural reforms of Russian gas industry. Price increases on domestic market have been considered as a remedy to overcome the risk of a shortage in Russian gas sector. Since then domestic gas prices have been following a steady upward trend. The average regulated gas prices for both industrial consumers and private households have more than doubled from 2006 to 2011 . Nonetheless, today Russian consumers pay one third of the gas price charged abroad.. The growing momentum for gas price liberalization in Russia is increasingly constrained by fears of potentially strong adverse impact that market-based price setting principle will have on the economy. Based on a novel multi-regional, multi-sector and multi-household computable general equilibrium (CGE) model of the Russian Federation, this paper presents a simple yet a flexible framework for evaluating gas price reform. We found that the reform is feasible at low economic cost, without greater disparities in terms of increased inequity within and between country's federal districts. Large redistributive impacts can arise from specific mechanisms to recycle revenues. In terms of global environmental credentials, gas price liberalization can bring Russia on a substantially more sustainable path. The potential to foster adoption of energy efficiency measures by exploiting the revenue-recycling effect is, however, limited.
Keywords: D58; H21; H22; Q48; 330; Regional general equilibrium model; sustainable development; natural gas pricing; Russia